Acceleration of Organic Waste Decomposition: A Comparative Study of ASEM-7 Decomposer Efficiency on Several Organic Wastes - Khalisha, Ana; Sari, Dwi Novanda; Sari, Stefina Liana; Sukmadewi, Rani; Pradipta, Adi Surya; Istyami, Astri Nur (Green Engineering Society, 2025)
Effective organic waste decomposition is vital for sustainable waste management and agricultural productivity. This study investigates the efficacy of ASEM-7—a newly developed decomposer comprising a consortium of seven microorganisms—in accelerating the composting process and enhancing compost quality across various types of organic waste. Five treatment groups were evaluated: paddy straw; animal manure; fruit and vegetable waste; a mixture of fruit and vegetable waste with straw; and a combination of fruit, vegetable waste, straw, and manure. During the decomposition process, key physicochemical parameters— including pH, temperature, moisture content, organic carbon (C-organic), total nitrogen (N-total), and the carbon-to-nitrogen (C/N) ratio—were systematically monitored. The results demonstrated that ASEM-7 significantly enhanced composting efficiency compared to both EM-4 and control (no-decomposer) treatments, achieving optimal pH stabilization (7–8) at a faster rate. Additionally, ASEM-7 reduced moisture content and C/N ratios more effectively, indicating a higher degree of compost maturity. Compost treated with ASEM-7 also exhibited the lowest levels of organic carbon, reflecting superior decomposition efficiency. Although temperature levels remained below the threshold required for effective pathogen elimination, microbial activity successfully facilitated nutrient recycling. The microbial consortium—comprising Bacillus sp., Lactobacillus sp., and Trichoderma sp.—demonstrated high efficacy in degrading recalcitrant organic materials such as straw and manure, thereby improving the compost's nutrient composition. By meeting key compost quality standards—organic carbon (≥15%), total nitrogen (≥0.5%), and a C/N ratio of 15–25—ASEM-7 effectively converts organic waste into high-quality compost. These findings underscore the importance of tailored microbial consortia in advancing sustainable waste management practices and enhancing soil fertility.